Mobile Voluntary Counseling Testing (VCT) pada Perkumpulan Keluarga Berencana Indonesia (PKBI) Daerah Bali: studi empiris dalam upaya penanganan HIV-AIDS - I Gusti Ngurah Pramesemara; Ninik Andrias; Dyah Pradnyaparamita Duarsa (DiscoverSys Inc., 2020)
Background: Nowadays, the transmission of HIV-AIDS is mostly due to risky sexual activity and found in the heterosexual group, around 76.5%. The high rate may be due to stigma and discrimination in society, so risk people are reluctant to come for a check-up or treatment. This study aims to evaluate the comprehensive approach from the upstream to downstream and culture based in dealing with HIV-AIDS in the form of Mobile Voluntary Counseling Testing (VCT) that has been carried out by the Indonesian Planned Parenthood Association (IPPA) Bali, Indonesia.Methods: This descriptive cross sectional study was conducted in the 2016-2018 period in all regions of Bali, Indonesia, by convenience sampling technique. There are differences in the total number of services that have been performed which include Post-Test (+) counselling, Post-Test Counseling (-), rapid test evaluation, HIV counselling and prevention measures, as well as VCT Pre-Test counselling. The medical team and counsellor came together to meet directly with groups at risk of HIV-AIDS infection called key populations, such as commercial sex workers, transvestites, drug users, and homosexuals. The data obtained were analyzed descriptively using Microsoft Excel for Windows.Results: The results of this descriptive empirical study show that the overall Post-Test (+) counselling was conducted 9 times in 2016 (2 times), 2017 (3 times), and 2018 (4 times). Whereas in Post-Test (-) counselling there were 161 examinations in 2016, 105 times (2017), and 125 (2018). In the last 3 years, 1,472 investigations have been carried out, of which 652 times were in 2016, 367 times in 2017, and 453 times in 2018.Conclusion: Mobile VCT of IPPA Bali may be one of the effective efforts in responding to the challenges of people who tend to be taboo and less concerned about sexual and reproductive health issues. Latar Belakang: Saat ini penularan HIV-AIDS sebagian besar disebabkan oleh aktivitas seksual yang berisiko dan ditemukan pada kelompok heteroseksual sekitar 76,5%. Tingginya angka tersebut mungkin disebabkan oleh stigma dan diskriminasi di masyarakat, sehingga orang yang berisiko enggan datang untuk melakukan pemeriksaan atau perawatan. Penelitian ini bertujuan untuk mengevaluasi pendekatan komprehensif dari hulu ke hilir dan budaya berbasis dalam berurusan dengan HIV-AIDS dalam bentuk Pengujian Konseling Sukarela Seluler (VCT) yang telah dilakukan oleh PKBI Bali, Indonesia.Metode: Penelitian deskriptif dengan pendekatan potong lintang ini dilakukan dalam rentang periode 2016-2018 di seluruh daerah Bali, Indonesia dengan menggunakan teknik convenience sampling. Terdapat perbedaan jumlah total layanan yang telah dilakukan dimana meliputi konseling Post-Test (+), Konseling Post-Test (-), evaluasi rapid test, konseling HIV dan tindakan pencegahan, maupun konseling VCT Pre-Test. Tim medis dan konselor datang bersama untuk bertemu langsung dengan kelompok yang berisiko terinfeksi HIV-AIDS yang disebut populasi kunci, seperti pekerja seks komersial, waria, pengguna narkoba, dan homoseksual. Data yang diperoleh dianalisis secara deskriptif menggunakan Microsoft Excel untuk Windows.Hasil: Hasil studi empiris deskriptif ini menunjukkan bahwa telah dilakukan 9 kali konseling Post-Test (+) baik pada tahun 2016 (2 kali), 2017 (3 kali), dan 2018 (4 kali). Sedangkan pada konseling Post-Test (-) terdapat 161 kali pemeriksaan pada tahun 2016, 105 kali (2017), dan 125 (2018). Secara keseluruhan dalam 3 tahun terakhir telah dilakukan sebanyak 1.472 pemeriksaan dimana sebanyak 652 kali pada tahun 2016, 367 kali pada tahun 2017, dan 453 kali pada tahun 2018.Kesimpulan: Mobile VCT PKBI Bali dapat menjadi salah satu upaya efektif dalam menanggapi tantangan orang-orang yang cenderung tabu dan kurang peduli tentang masalah kesehatan seksual dan reproduksi.